2011
DOI: 10.1590/s1984-29612011000300003
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and attitudes among milk producers in Minas Gerais regarding cattle tick biology and control

Abstract: This study evaluates milk producers' knowledge regarding cattle ticks and practices for controlling them. Ninetythree dairymen in Minas Gerais were interviewed. These producers had no information regarding acaricide efficiency tests. To analyze the information, open responses were categorized through "content analysis", and descriptive analysis consisting of extracting the profile highlighted by the highest frequencies. The association between schooling level and knowledge was tested by means of chi-square tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 7 publications
1
14
0
2
Order By: Relevance
“…While this association may seem unexpected at first glance, it might be inferred that farms treating their cattle should have higher tick infestations. In Brazil, the vast majority of farmers use manual backpack sprayers for applying acaricides on cattle, which usually results in incorrect application under field conditions, and consequently, inefficient tick control (AMARAL et al, 2011). In the present study, all the farmers who reported that they sprayed their cattle also reported that they used backpack sprayers (data not shown).…”
Section: Discussionmentioning
confidence: 46%
“…While this association may seem unexpected at first glance, it might be inferred that farms treating their cattle should have higher tick infestations. In Brazil, the vast majority of farmers use manual backpack sprayers for applying acaricides on cattle, which usually results in incorrect application under field conditions, and consequently, inefficient tick control (AMARAL et al, 2011). In the present study, all the farmers who reported that they sprayed their cattle also reported that they used backpack sprayers (data not shown).…”
Section: Discussionmentioning
confidence: 46%
“…Agribusiness represents one-third of Brazilian gross domestic product (PIB), and in this sense, the cattle raising represents one of the main branches, once Brazil is amidst the largest producers of meat and dairy products. In opposite, one of the main limitations for Brazilian cattle breeding is the economic loss occasioned by ticks [13,9].…”
Section: Introductionmentioning
confidence: 99%
“…The chemical control is currently the preferred for the combat of ticks; however, the incorrect use of this method favors the occurrence of multiple or cross resistance [7,8]. In addition, the permanence of residues in animals and their products, thereby, alternatives to the control of this parasite are highly relevant [9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations